2014
DOI: 10.1038/nm.3599
|View full text |Cite
|
Sign up to set email alerts
|

An epithelial circadian clock controls pulmonary inflammation and glucocorticoid action

Abstract: The circadian system is as an important regulator of immune function. Human inflammatory lung diseases frequently show time-of-day variation in symptom severity and lung function, but the mechanisms and cell types that are underlying these effects remain unclear. We show that pulmonary antibacterial responses are modulated by a circadian clock within epithelial club (Clara) cells. These drive circadian neutrophil recruitment to the lung via the chemokine CXCL5. Genetic ablation of the clock gene Bmal1 (also ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
424
6
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(477 citation statements)
references
References 49 publications
21
424
6
4
Order By: Relevance
“…These immune cell clocks could act in two ways: by regulating the expression of molecules important for the synthesis and secretion of cytokines by these cells and by gating the response to the regulatory effects of cues from the central clock. A local direct regulation of immune cell functions (25,28) and a gating of the response to systemic cues (14,58,59) were shown to occur in rodents. However, we cannot exclude that the shift in the sleep-wake/feeding cycle might have contributed, to some extent, to the changes observed in the cytokine-release rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…These immune cell clocks could act in two ways: by regulating the expression of molecules important for the synthesis and secretion of cytokines by these cells and by gating the response to the regulatory effects of cues from the central clock. A local direct regulation of immune cell functions (25,28) and a gating of the response to systemic cues (14,58,59) were shown to occur in rodents. However, we cannot exclude that the shift in the sleep-wake/feeding cycle might have contributed, to some extent, to the changes observed in the cytokine-release rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, clock dysfunction in the lungs may explain increased COPD exacerbations in patients presenting at night and in the early morning hours when lung function is low (1). These effects may be due to circadian disruption in peripheral tissues and/or uncoupling between peripheral oscillators and the master clock located in the suprachiasmatic nucleus of the hypothalamus (5)(6)(7)(8). By examining the direct effects of smoking and COPD on molecular clock gene expression in peripheral oscillators, we can dissect the impact of environmental stress on cell-autonomous clocks and begin to describe the mechanism linking clock disruption to enhanced inflammatory responses (9).…”
mentioning
confidence: 99%
“…This suggests the involvement of the SIRT1-BMAL1 signaling pathway in CS-induced lung inflammation and circadian dysfunction. Accumulating evidence indicates that monocytes/ macrophages and epithelial cells show a daily variation of inflammatory immune responses to environmental stress (5,(17)(18)(19). However, it is not known whether circadian clock function is disrupted in smokers and patients with COPD and whether these responses can be regulated by SIRT1.…”
mentioning
confidence: 99%
“…For example, the circadian rhythm observed in glucocorticoid hormones have been found to be linked with the magnitude of pulmonary inflammation. 7 In addition, the periodic variations in levels of melatonin indirectly affects inflammatory reaction. 8 Mattana et al reported that patients who underwent HD late in the day had relatively higher levels of potassium and phosphorus than those dialyzed earlier in the day.…”
Section: Discussionmentioning
confidence: 99%